Challenges of site-specific selenocysteine incorporation into proteins by Escherichia coli. Issue 4 (4th May 2018) - Fu, Xian; Söll, Dieter; Sevostyanova, Anastasia
ABSTRACT: Selenocysteine (Sec), a rare genetically encoded amino acid with unusual chemical properties, is of great interest for protein engineering. Sec is synthesized on its cognate tRNA (tRNA Sec ) by the concerted action of several enzymes. While all other aminoacyl-tRNAs are delivered to the ribosome by the elongation factor Tu (EF-Tu), Sec-tRNA Sec requires a dedicated factor, SelB. Incorporation of Sec into protein requires recoding of the stop codon UGA aided by a specific mRNA structure, the SECIS element. This unusual biogenesis restricts the use of Sec in recombinant proteins, limiting our ability to study the properties of selenoproteins. Several methods are currently available for the synthesis selenoproteins. Here we focus on strategies for in vivo Sec insertion at any position(s) within a recombinant protein in a SECIS-independent manner: (i) engineering of tRNA Sec for use by EF-Tu without the SECIS requirement, and (ii) design of a SECIS-independent SelB route.